2022
DOI: 10.1177/01939459221134374
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Literature Review of Rural Beliefs and Attitudes toward Telehealth Utilization

Abstract: The purpose of this scoping literature review was to understand what is known about how the rural profile influences beliefs regarding telehealth utilization. Rural nursing theory (RNT) provided a framework for the review. Search criteria were limited to peer-reviewed studies conducted in Europe, the United States, Canada, Australia, and New Zealand. A variety of search terms related to patient telehealth perceptions generated 213 unique articles, of which 10 met the inclusion criteria. Included studies incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…The perceived technological possibilities to improve access can have unintended consequences for community members which may contribute to lack of responsiveness to community needs (8). It is therefore important to understand the client and their preferences for using telehealth rather than making assumptions on the appropriateness of this type of health service delivery (21). As such, telehealth is likely to function best when there is a pre-established relationship between the client and clinician, with clients who have a good knowledge of their personal health, and have access to and familiarity with digital technology (22).…”
Section: Discussionmentioning
confidence: 99%
“…The perceived technological possibilities to improve access can have unintended consequences for community members which may contribute to lack of responsiveness to community needs (8). It is therefore important to understand the client and their preferences for using telehealth rather than making assumptions on the appropriateness of this type of health service delivery (21). As such, telehealth is likely to function best when there is a pre-established relationship between the client and clinician, with clients who have a good knowledge of their personal health, and have access to and familiarity with digital technology (22).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that telehealth services are effective in the management of physical and psychological conditions post‐cancer treatment, such fatigue and cognitive disfunction 71 . A recent review suggests that telehealth is a well‐accepted alternative to face‐to‐face healthcare for people living in rural areas as long as consideration is given to aspects such as privacy, trust and the patient's access to resources 72 . To facilitate these solutions, better internet and phone connectivity is needed in remote areas 73 and healthcare providers need comprehensive, up to date, and simple to use referral directories and processes 74 …”
Section: Discussionmentioning
confidence: 99%
“…This study clari ed the effects of privacy issues on social interactions among rural people, which is critical for the continuity of rural communities. Previous studies have shown that privacy issues can cause a loss of intimacy among people in communities because they fail to share personal information [33,34]. Although people can protect their privacy, interdependent conditions requiring mutual help have decreased in communities [35], and decreased mutual help affects rural people's health [36].…”
Section: Discussionmentioning
confidence: 99%